Dispute resolution in E-transaction in Palestine - Hasan, Yahya Y. F.; Zulhuda, Sonny (South East Asia Journal of Business Economics and Law, 2016)
E-transaction has become a familiar way to purchase goods and services, and there are many people or companies that prefer purchasing goods on the Internet. This new phenomenon leads to many types of disputes between the parties within the period of contracting, or in the period of enforcing contracts. There are many types of disputes that might arise between the parties in e-transactions, such as the failure to deliver the goods, submission of defective goods, failure to complete payment, and the loss of payment. All of these disputes require resolution, and the injured party can claim damages from the courts, but this might be impeded by the competency of the courts, as the parties involved might be from different countries, which makes resolution infinitely more complicated. Therefore, these disputes require suitable resolution for a new environment of e-transaction. This paper will discuss the alternative dispute resolution which enable the parties to conclude an agreement to resolve these disputes via alternative means such as arbitration and mediation. In addition, this paper seeks to clarify some methods of resolving disputes such as Alternative dispute resolution (ADR) including arbitration and mediation, and also online dispute resolution (ODR) including online Arbitration and online mediation. This study mainly used the analytical and library research to examine the main issues of Dispute resolution in e-transaction in Palestine. The laws of Palestine, the Directive 2008/11/EU, and Directive 2013/52/EC are used in this study to clarify the legal positions on the relevant issues above. It is found from this study that the current laws in Palestine organize the arbitration as an alternative to dispute resolutions, but these laws are inadequate to regulate the other types of alternative dispute resolution, such as mediation. The parties can write the clause of arbitration by data message, and include the clause of arbitration in e-transaction contracts because the law allows electronic means of writing arbitration agreement. The arbitration decision requires the affirmance from the competent court before it becomes binding according to the Palestinian Arbitration Law. The decision of arbitration becomes binding after the court affirms it, and the parties are obliged to enforce it. The role of a mediator is different from the role of an arbitrator, because the arbitrator can decide on the solution, and the parties are obligated to implement this solution. Furthermore, in arbitration, the parties sign an agreement to resolve their dispute via arbitration, and this agreement is binding. The benefit of this paper is to propose some recommendations to develop the Palestinian laws in order to address the issues of mediation besides arbitration as an alternative to resolve disputes in e-transaction contracts which will contribute in the development of e-commerce in Palestine.